Qualitative study of self-concept in adolescents from divorced families - Tan, Trina Li Lian. (2008)
The primary objective of this study was to investigate if there was any change in the self-concept of adolescents with the occurrence of a divorce in the family. The adolescents were four students from the same school. The school is a co-educational secondary school. The students were all currently undergoing counseling with the author to help them cope with the divorce and the effects arising from the divorce. Three of the subjects were girls, with only one boy. Out of these four subjects, only the 15-year-old girl and the 17-year-old boy have been referred by the teachers to see the school counselor.